Precise structures and anti-intrinsic tenase complex activity of three fucosylated glycosaminoglycans and their fragments. (15th November 2019) - Cai, Ying; Yang, Wenjiao; Li, Xiaomei; Zhou, Lutan; Wang, Zhongjuan; Lin, Lisha; Chen, Dingyuan; Zhao, Longyan; Li, Zhongkun; Liu, Shubai; Yin, Ronghua; Zuo, Zhili; et al.
Highlights: Three FGs were isolated from three species of sea cucumbers. The structures ofA1 -A4, H1 -H4 andS1 -S4 from depolymerized FGs were determined. Three FGs were deduced as -{→4)-[ L -FucS-α(1→3)]- D -GlcA-β(1→3)- D - GalNAc4S6S -β(1}n-. The effects of fucose types on anti-intrinsic tenase activity were discussed. Abstract: Fucosylated glycosaminoglycan (FG), a glycosaminoglycan derivative containing distinct sulfated fucose (FucS) branches, displays potent anticoagulant activity by inhibiting the intrinsic tenase complex (iXase). Herein, AmFG, SvFG and HaFG from three species of sea cucumbers were isolated and depolymerized by β-eliminative cleavage. Three series of fragments, A1 -A4, S1 -S4 andH1 -H4, were purified from the depolymerized FGs. Based on structural analysis of these fragments, three FGs were deduced as -{→4)-[ L -FucS-α(1→3)]- D -GlcA-β(1→3)- D -GalNAc4S6S -β(1}n -. The structures differed in sulfation types of FucS, namely, most of FucS in AmFG was Fuc3S4S, but the FucS in SvFG was Fuc2S4S, while the FucS in HaFG was Fuc3S4S, Fuc2S4S and Fuc4S . However, all FucS branches attached to C -3 of GlcA as monosaccharides. Anticoagulant and anti-iXase assays showed the octasaccharide is the minimum fragment for potent anticoagulant activity via anti-iXase irrespective of FucS types. Among FG fragments with same degree of polymerization, oligosaccharides containing Fuc2S4S had more potent anti-iXase activity.